Stress and Anxiety Levels of International Nursing Students: Case of Northern Cyprus - Samineh Esmaeilzadeh; Kemal Elyeli; Sandra Chıkwana (Sağlık Bilimleri Üniversitesi Hemşirelik Dergisi)
Introduction: Stress is a multifaceted concept that focuses on changes in the interaction between people and their environment. Stress, which is increasing in developing and rich countries, is one of the biggest problems affcting the health sector, especially universities, and especially nursing practices.Aim: This study aimed to determine the stress and anxiety levels of undergraduate nursing students.Method: This descriptive study was conducted on 223 international nursing students studying at Near East University to determine the stress and anxiety levels of nursing students. Data were collected through online Google Forms using the Generalized Anxiety Disorder - 7 Scale, Perceived Stress Scale and Sociodemographic questionnaire in December 2022 and January 2023.Results: Of the students participating in this study, 182 (81.6%) were female and 41 (18.4%) were male. Students' average Perceived Stress Scale score was 22.00 ± 8.52; Generalized Anxiety Disorder -7 Scale mean score were found to be 7.43 ± 6.43. Perceived Stress Scale average scores vary depending on students' grade point averages and alcohol/substance use while under stress. Generalized Anxiety Disorder - 7 Scale mean scores vary depending on alcohol/ substance use while under stress (p lt; 0.05).Conclusion: Educational programs should be organized to enable students to cope more effctively with the stressors they encounter. On the other hand, it is recommended to create learning environments that will help alleviate the stress and anxiety that students encounter during the education process.